Preparation and application of a novel separation membrane column based on multiple green adsorbents for synergistic decontamination

CN122977503APending Publication Date: 2026-10-27NANCHANG HANGKONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611328625.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

上述污染物共存于工业废水中,形成复合污染:重金属(如铜、铬、铅等)化学性质稳定、不可生物降解,易在水生生物体内富集并沿食物链放大,具有致癌、致畸及神经毒性;氨氮在水体中经微生物硝化作用大量消耗溶解氧,导致水生生物缺氧死亡,且非离子氨对鱼类具有直接毒害作用;磷作为限制性营养元素,过量输入会引发水体富营养化,诱发蓝藻水华或赤潮,破坏水生生态系统平衡

Benefits of technology

其一,以废弃醋酸纤维素膜为原料经预氧化与氮气氛围下高温焙烧制备 N 掺杂生物炭,实现了固体废弃物的资源化利用,降低了原料成本,且 N 掺杂可丰富生物炭表面含氮官能团与孔隙结构,显著提升对重金属离子的吸附容量;其二,采用单针共混电纺丝技术制备醋酸纤维素/壳聚糖复合纤维膜,具有高比表面积与丰富的氨基、羟基等活性基团,可通过配位与化学螯合作用高效深度净化水体重金属;其三,Fe 掺杂沸石与天然沸石共混形成的混合沸石,借助 Fe3+对磷的特异性配位沉淀作用及沸石的离子交换能力,可实现对氨氮和磷的高效去除;其四,三种绿色吸附剂自上而下分层装载于多段式膜柱中,形成分级协同去污体系,可在同一装置内同步去除复杂工业废水中的重金属、氨氮及磷,解决了传统方法难以同步处理复合污染物的技术问题;其五,装置采用多段筒体拼接与滤板螺丝固定结构,拆装简便,便于吸附剂的更换与回收,且整体成本低廉、环境友好,具有良好的工业化应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977503A_ABST
    Figure CN122977503A_ABST
Patent Text Reader

Abstract

The application discloses a novel separation membrane column based on a variety of green adsorbents for synergistic decontamination, and belongs to the field of industrial wastewater treatment. The membrane column is composed of N-doped biochar prepared from waste cellulose acetate membrane, cellulose acetate / chitosan composite fiber membrane prepared by electrospinning, and a blend of Fe-doped zeolite and natural zeolite, which are loaded in layers in a detachable hollow cylindrical cylinder, and water treatment is achieved by circulating filtration with a water pump. The application adopts a relay purification mechanism of "activated carbon pretreatment-composite membrane heavy metal removal-mixed zeolite denitrification and phosphorus removal", and the materials are derived from waste or green renewable resources, which conforms to the concept of sustainable development. The device has a compact structure, can be flexibly assembled and disassembled, occupies a small area, can efficiently remove suspended solids, heavy metals, ammonia nitrogen and phosphorus in water, has the advantages of simple operation, high efficiency and low cost, is suitable for various industrial wastewater scenes, and has a broad industrialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of complex industrial wastewater treatment, and in particular relates to the preparation and application of a novel separation membrane column based on the synergistic decontamination of multiple green adsorbents. Background Technology

[0002] With the rapid development of industries such as mining, metallurgy, chemicals, textiles, and agricultural and sideline food processing, while improving people's well-being, a large amount of complex industrial wastewater containing heavy metals, ammonia nitrogen, and phosphorus is discharged into the aquatic environment. Among them, the three major industries of non-ferrous metal mining and beneficiation, metal products, and non-ferrous metal smelting account for 46.76% of industrial heavy metal emissions, while the three major industries of agricultural and sideline food processing, chemical raw material manufacturing, and food manufacturing account for 55.61% of total industrial phosphorus emissions. Ammonia nitrogen emissions are mainly concentrated in industries such as chemical raw materials and chemical products manufacturing. The aforementioned pollutants coexist in industrial wastewater, forming a complex pollution: heavy metals (such as copper, chromium, and lead) are chemically stable and non-biodegradable, easily accumulating in aquatic organisms and amplifying along the food chain, exhibiting carcinogenic, teratogenic, and neurotoxic effects; ammonia nitrogen consumes large amounts of dissolved oxygen in water bodies through microbial nitrification, leading to hypoxia and death of aquatic organisms, and non-ionic ammonia has a direct toxic effect on fish; phosphorus, as a limiting nutrient element, can cause eutrophication when excessively introduced, inducing cyanobacterial blooms or red tides, and disrupting the balance of aquatic ecosystems. The coexistence of these three pollutants can also produce synergistic toxic effects, further exacerbating the threat to the ecological environment and human health. Therefore, developing treatment technologies that can simultaneously and efficiently remove heavy metals, ammonia nitrogen, and phosphorus from complex industrial wastewater has become a crucial technical problem urgently needing to be solved in the field of water pollution control.

[0003] Common treatment methods are mostly designed for single pollutants. Furthermore, common chemical precipitation methods produce large amounts of sludge and are prone to secondary pollution; biological methods are greatly affected by water quality fluctuations and have poor tolerance to heavy metals; adsorption methods only achieve phase transfer of pollutants rather than complete removal and have high regeneration costs, making it difficult to simultaneously, efficiently, and stably remove combined pollution of heavy metals, ammonia nitrogen, and phosphorus in the same system. Considering that ammonia nitrogen, heavy metals, and phosphorus are high-value resources, while sedimentation and biodegradation methods can achieve emission standards, they lead to a large amount of resource waste each year, which is inconsistent with the sustainable development concept advocated by the times.

[0004] Against this backdrop, adsorption methods are favored due to their high efficiency, convenience, and resource recovery. Adsorption membranes, a type of separation membrane technology, utilize the active adsorption sites on their high specific surface area and within the membrane to achieve targeted capture of heavy metal ions within the same system. They offer advantages such as high separation efficiency, stable effluent quality, small footprint, and modular integration, demonstrating promising application potential in the advanced treatment of complex industrial wastewater.

[0005] However, existing adsorption separation membrane technologies still have the following shortcomings: the membrane materials have limited selective retention capacity for small molecule pollutants such as ammonia nitrogen and phosphorus, often requiring other means to achieve effective removal, resulting in a significant increase in operating energy consumption and costs; heavy metal deposition, organic matter adsorption, and microbial growth in wastewater can easily cause severe membrane fouling, leading to a continuous decline in flux; at the same time, membrane technology only achieves phase transfer of pollutants rather than complete degradation, making subsequent treatment of concentrated wastewater difficult, and the membrane materials are expensive and require frequent replacement, thus restricting their economic feasibility and long-term stability in the large-scale treatment of industrial wastewater containing heavy metals, ammonia nitrogen, and phosphorus.

[0006] To address the aforementioned issues, we introduced nitrogen-doped activated carbon at the upstream end of the cellulose acetate / chitosan composite fiber membrane for pretreatment of the composite wastewater. This reduces the erosion, pollution, and direct damage to the membrane in complex environments, enhancing its resistance. To address the low removal rates of ammonia nitrogen and phosphorus by the composite fiber membrane, we introduced mixed zeolite at the downstream end. Through deposition and ion exchange, ammonia nitrogen and phosphorus are adsorbed and recovered. Ultimately, through a relay treatment approach of "activated carbon pretreatment," "composite membrane purification of heavy metals," and "mixed zeolite removal of nitrogen and phosphorus," combined with an engineered, adaptable, detachable, layered, lightweight integrated adsorption column, and through circulating filtration, we can efficiently achieve comprehensive treatment of suspended solids, heavy metals, ammonia nitrogen, and phosphorus in water bodies, demonstrating broad market prospects and economic value. Summary of the Invention

[0007] To address the aforementioned problems, this invention proposes a novel method for preparing a separation membrane column based on the synergistic decontamination of multiple green adsorbents, achieving a technological breakthrough. The specific solution is as follows: This invention discloses a novel separation membrane column based on the synergistic decontamination of multiple green adsorbents, characterized in that the assembly of the device includes the following steps: S1. A certain amount of waste cellulose acetate membrane is pre-oxidized at low temperature in a muffle furnace for a period of time to improve the oxygen content of the membrane material and protect the structure of the carbonized membrane. Then it is placed in a tube furnace, mixed with urea, and calcined at high temperature under a nitrogen atmosphere and naturally cooled to prepare N-doped biochar required for water pretreatment. S2, by electrospinning technology, 5 wt% cellulose acetate solution and 5 wt% chitosan solution were mixed evenly, taken out with a syringe, and then spun onto baking paper using single-needle blending electrospinning technology under a stable voltage and at a uniform speed to prepare a composite fiber membrane of cellulose acetate / chitosan with high specific surface area and high active groups. S3. A certain amount of natural zeolite is soaked in a mixed solution containing NaCl and FeCl3. Under water bath conditions, the natural zeolite is treated while stirring, so that NaCl and FeCl3 completely penetrate into the pores of the natural zeolite. Then the zeolite is placed in a crucible and rapidly calcined in a muffle furnace to obtain the desired Fe-doped zeolite. S4. Finally, from top to bottom, N-doped biochar, cellulose acetate / chitosan composite fiber membrane, and Fe-doped zeolite and natural zeolite are loaded into the hollow cylindrical body or the seam of the distillation tower. Then, the three sections of the cylinder are connected to the base with screws. A water supply pipe connected to the water pump is connected to the water inlet of the base, and a water outlet pipe connected to the storage tank extends from the top. The assembly is then completed.

[0008] Furthermore, this invention discloses a preparation process for preparing N-doped activated carbon based on the carbonization of waste cellulose acetate membrane, with the following specific features: The N-doped biochar is obtained by continuously pre-oxidizing 25g of waste cellulose acetate membrane in a crucible and a porcelain boat in a muffle furnace and then calcining it in a tube furnace under a nitrogen atmosphere. Preferably, during the roasting process in the muffle furnace, the heating rate is 2.5-3℃ / min, the holding temperature is 280℃, the holding time is 2-3h, and then it is naturally cooled. Preferably, during the roasting process in the tube furnace, under a nitrogen atmosphere, the heating rate is 1.5-2℃ / min, the holding temperature is 800℃, the holding time is 4h, and then it is naturally cooled.

[0009] More preferably, the waste cellulose acetate membrane obtained after the N-doped biochar pre-oxidation treatment needs to be ground and mixed with urea at a mass ratio of 1:1 for 10 minutes before being placed into the tube furnace, and then poured into a ceramic boat; Furthermore, this invention discloses a preparation process for a cellulose acetate / chitosan composite fiber membrane, with the following specific features: Preferably, the cellulose acetate / chitosan composite fiber membrane is based on a 5wt% cellulose acetate solution and a 5wt% chitosan solution, and the mass ratio of the two solutions is 1:1 when they are mixed. Preferably, the cellulose acetate / chitosan composite fiber membrane has the following components: a 5 wt% cellulose acetate solution obtained by dissolving 3.084 g of cellulose acetate in 50 mL of acetic acid / dichloromethane; and a 5 wt% chitosan solution obtained by dissolving 2.53 g of chitosan in 50 mL of high-concentration acetic acid solution. More preferably, the volume ratios of the two mixed solvents in the cellulose acetate / chitosan composite fiber membrane are acetic acid: dichloromethane = 1:2 and acetic acid: deionized water = 9:1. Preferably, the specific parameters for electrospinning are: temperature 15-25℃, humidity 50%, positive spinning voltage 18kV, negative spinning voltage -2.5kV, spinning rate 0.15-0.25mm / min, distance between spinneret and receiver 18cm, and spinning time 1-3h.

[0010] Furthermore, this invention discloses a preparation process for mixed zeolites, the specific steps of which are as follows: Preferably, the mixed zeolite is obtained by blending and grinding large-particle natural zeolite and Fe-doped zeolite at a mass ratio of 2:1, and then sieving it through a 200-mesh sieve.

[0011] Preferably, the preparation process of the Fe-doped zeolite is as follows: First, add large-particle natural zeolite to a mixed solution of NaCl and FeCl3 at a ratio of 10g / 100mL, and then react in a water bath at 80℃ and 200-300r / min for 1 hour. More preferably, the mixed solution of NaCl and FeCl3 is prepared by mixing 10% FeCl3 solution and 10% NaCl solution in a volume ratio of 1:1. Preferably, the Fe-doped zeolite is calcined in a muffle furnace with a heating rate of 3-5℃ / min, a holding temperature of 400-500℃, a holding time of 1.5-2.5h, and then naturally cooled. This invention discloses a method for assembling a novel separation membrane column that synergistically removes contaminants using multiple green adsorbents. The specific steps are as follows: Preferably, a novel separation membrane column based on the synergistic decontamination of multiple green adsorbents is characterized in that the loaded N-doped biochar, cellulose acetate / chitosan composite fiber membrane and Fe-doped zeolite and natural zeolite are mixed zeolite, respectively filled in according to a certain mass-volume ratio with the wastewater. More preferably, the N-doped biochar is 15-25 g / L, the composite fiber membrane is 1-2 g / L, and the mixed zeolite is 7-15 g / L.

[0012] Preferably, a novel separation membrane column based on the synergistic decontamination of multiple green adsorbents is characterized by... The device column is made up of multiple hollow cylindrical columns, and the dimensions, wall thickness and height of each cylinder are the same. More preferably, the upper and lower ends of the middle section of the cylinder are both porous filter plates, which can be used to fix the composite fiber membrane by clamping on both sides. More preferably, the N-doped biochar is placed at the top of the hollow column, with an inlet and a removable cover at the top and a microfiltration-grade porous filter plate at the bottom. Preferably, the composite fiber membrane has a microfiltration-grade porous filter plate at the joint between the middle and upper sections and the middle and lower sections of the two cylinders, and a coarse filtration-grade porous filter plate at the lower cylinder. Preferably, the mixed zeolite is located at the bottom of the semi-enclosed hollow cylinder, while the upper part is a coarse filtration stage porous filter plate; the filter plate and the cylinder are integrated. Preferably, each filter plate is slightly wider than the cylinder itself, and the filter plates are fixed to each other at the outer edge of the filter plates by screws; the base is fixed in the same way as the lower section.

[0013] The present invention has the following beneficial effects: Firstly, nitrogen-doped biochar was prepared from waste cellulose acetate membranes through pre-oxidation and high-temperature calcination under a nitrogen atmosphere, realizing the resource utilization of solid waste, reducing raw material costs, and enriching the nitrogen-containing functional groups and pore structure on the biochar surface, significantly improving the adsorption capacity for heavy metal ions. Secondly, cellulose acetate / chitosan composite fiber membranes were prepared using single-needle blending electrospinning technology, possessing high specific surface area and abundant active groups such as amino and hydroxyl groups, which can efficiently and deeply purify heavy metals in water through coordination and chemical chelation. Thirdly, mixed zeolite formed by blending Fe-doped zeolite with natural zeolite, utilizing Fe... 3+ The specific coordination precipitation of phosphorus and the ion exchange capacity of zeolite enable efficient removal of ammonia nitrogen and phosphorus. Fourth, three green adsorbents are layered and loaded in a multi-segment membrane column from top to bottom to form a graded synergistic decontamination system, which can simultaneously remove heavy metals, ammonia nitrogen and phosphorus from complex industrial wastewater in the same device, solving the technical problem that traditional methods cannot treat complex pollutants simultaneously. Fifth, the device adopts a multi-segment cylindrical splicing and filter plate screw fixing structure, which is easy to disassemble and assemble, facilitates the replacement and recycling of adsorbents, and has low overall cost and environmental friendliness, with good prospects for industrial application. Attached Figure Description

[0014] Figure 1 This is a cross-sectional view and specific parameters of the core structure of the novel separation membrane column based on the synergistic decontamination of multiple green adsorbents; Figure 2 This image shows the physical membrane column and complete equipment flow diagram of this novel separation membrane column based on the synergistic decontamination of multiple green adsorbents. Figure 3 This table presents experimental data for a novel separation membrane column based on the synergistic decontamination of multiple green adsorbents under different conditions. Detailed Implementation

[0015] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to embodiments and accompanying drawings: Example 1

[0016] To prepare simulated wastewater, add 25 mg of Cu2+, Pb2+, and Ni2+, 50 mg of NH4+, and 10 mg of PO43- to 1 L of deionized water.

[0017] A novel separation membrane column based on the synergistic decontamination of multiple green adsorbents is prepared as follows: Place 25g of waste cellulose acetate membrane in a crucible, heat it to 280℃ in a muffle furnace at a rate of 2.5-3℃ / min, hold it at that temperature for 2-3 hours for pre-oxidation, and finally let it cool naturally. The pre-oxidized waste cellulose acetate membrane was ground and mixed with urea at a mass ratio of 1:1 for 10 minutes. Then it was placed in a ceramic boat in a tube furnace and heated to 800℃ at a rate of 1.5-2℃ / min under a nitrogen atmosphere. After holding at this temperature for 4 hours, it was finally cooled naturally. The carbonized membrane was then crushed to obtain the desired N-doped biochar.

[0018] Dissolve 3.084 g of cellulose acetate in 50 mL of acetic acid / dichloromethane (acetic acid:dichloromethane = 1:2) to obtain the desired 5 wt% cellulose acetate solution; dissolve 2.53 g of chitosan in 50 mL of high-concentration acetic acid solution (acetic acid:deionized water = 9:1) to obtain the desired 5 wt% chitosan solution; then prepare 20 g of spinning solution by mixing the 5 wt% chitosan solution and the 5 wt% cellulose acetate solution in a 1:1 mass ratio. Electrospinning was performed using a 10mL needle with approximately 5.12g of spinning solution. The specific parameters for electrospinning were as follows: a 21G needle was used; the ambient temperature was 15-25℃ and the humidity was 50%; the positive spinning voltage was 18kV; the negative spinning voltage was -2.5kV; the spinning rate was 0.15-0.25mm / min; the distance between the spinneret and the receiver was 18cm; and the spinning time was 1-3h.

[0019] At a ratio of 10g / 100mL, 10g of large-particle natural zeolite was added to 100mL of a mixed solution of 10% NaCl and 10% FeCl3. The reaction was carried out in a water bath at 80℃ and 200-300r / min for 1 hour. It is then transferred to a muffle furnace, heated at 3-5℃ / min to 400℃, held at that temperature for 2.5h, and then cooled naturally to obtain the desired Fe-doped zeolite. The mixture is made by blending and grinding large-particle natural zeolite and Fe-doped zeolite at a mass ratio of 2:1; and then sieving through a 200-mesh sieve to obtain the required 27.8g of mixed zeolite.

[0020] The N-doped biochar, cellulose acetate / chitosan composite fiber membrane, and Fe-doped zeolite and natural zeolite mixed zeolite were filled in according to a certain mass-volume ratio with the wastewater. Finally, 20g of nitrogen-doped biochar, approximately 1g of composite fiber membrane fixed on both sides of the middle section, and a mixed zeolite consisting of 10g of Fe-doped zeolite and natural zeolite are loaded from top to bottom into the hollow cylindrical body resembling a distillation tower or between the seams of the cylinder. The three sections of the cylinder are then connected to the base with screws. A water inlet pipe connected to a water pump is connected to the inlet of the base, and an outlet pipe extending from the top connects to the storage tank. This completes the assembly. The solution is then slowly pumped in at a rate of 100mL / min for 2 hours of circulating filtration. For specific results, see [link to product description]. Figure 3 .

[0021] Example 2

[0022] Compared to Example 1, only the preparation and loading of N-doped activated carbon were no longer performed; all other conditions remained the same as in Example 1. Specific effects can be found in [link to example]. Figure 3 .

[0023] Example 3

[0024] Compared to Example 1, the only difference was that the cellulose acetate / chitosan composite fiber membrane was no longer prepared; all other conditions remained the same as in Example 1. For specific results, see [link to example]. Figure 3 .

[0025] Example 4

[0026] Compared to Example 1, the only difference is that the mixture with the load is no longer prepared; all other conditions are the same as in Example 1. See below for specific results. Figure 3 .

[0027] In summary, this invention provides a novel separation membrane column based on the synergistic removal of pollutants using multiple green adsorbents. Through a three-stage relay treatment strategy of "activated carbon pretreatment – ​​composite membrane purification of heavy metals – mixed zeolite removal of nitrogen and phosphorus," N-doped biochar, cellulose acetate / chitosan composite fiber membrane, and a mixture of Fe-doped zeolite and natural zeolite are layered from top to bottom within a multi-segment hollow column, achieving simultaneous and efficient removal of suspended solids, heavy metals, ammonia nitrogen, and phosphorus from complex industrial wastewater. Specifically, the N-doped biochar uses waste cellulose acetate membrane as raw material, combining waste resource utilization and pretreatment functions; the electrospun composite fiber membrane deeply captures heavy metals due to its high specific surface area and abundant active groups; and the Fe-doped mixed zeolite efficiently removes ammonia nitrogen and phosphorus through ion exchange and coordination precipitation. This membrane column device has a simple structure, is detachable and assembleable, occupies a small area, and uses environmentally friendly adsorbent raw materials that are easy to replace and recycle. It provides an efficient, economical, and sustainable new technological approach for the treatment of complex industrial wastewater containing heavy metals, ammonia nitrogen, and phosphorus, and has good prospects for industrial application.

[0028] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A novel separation membrane column based on the synergistic decontamination of multiple green adsorbents, characterized in that, The assembly of this device includes the following steps: S1. A certain amount of waste cellulose acetate membrane is pre-oxidized at low temperature in a muffle furnace for a period of time to improve the oxygen content of the membrane material and protect the structure of the carbonized membrane. Then it is placed in a tube furnace, mixed with urea, and calcined at high temperature under a nitrogen atmosphere and naturally cooled to prepare N-doped biochar required for water pretreatment. S2, by electrospinning technology, 5 wt% cellulose acetate solution and 5 wt% chitosan solution were mixed evenly, taken out with a syringe, and then spun onto baking paper using single-needle blending electrospinning technology under a stable voltage and at a uniform speed to prepare a composite fiber membrane of cellulose acetate / chitosan with high specific surface area and high active groups. S3. A certain amount of natural zeolite is soaked in a mixed solution containing NaCl and FeCl3. Under water bath conditions, the natural zeolite is treated while stirring, so that NaCl and FeCl3 completely penetrate into the pores of the natural zeolite. Then the zeolite is placed in a crucible and rapidly calcined in a muffle furnace to obtain the desired Fe-doped zeolite. S4. Finally, from top to bottom, N-doped biochar, cellulose acetate / chitosan composite fiber membrane, and Fe-doped zeolite and natural zeolite are loaded into the hollow cylindrical body or the seam of the distillation tower. Then, the three sections of the cylinder are connected to the base with screws. A water supply pipe connected to the water pump is connected to the water inlet of the base, and a water outlet pipe connected to the storage tank extends from the top. The assembly is then completed.

2. The novel separation membrane column based on the synergistic decontamination of multiple green adsorbents according to claim 1, characterized in that, The nitrogen-doped biochar is roasted in a muffle furnace at a heating rate of 2.5-3℃ / min, a holding temperature of 280℃, and a holding time of 2-3 hours, followed by natural cooling. In a tube furnace, under a nitrogen atmosphere, the heating rate is 1.5-2℃ / min, the holding temperature is 800℃, and the holding time is 4 hours, followed by natural cooling. The nitrogen-doped biochar is blended with urea at a mass ratio of 1:1 for pre-oxidized waste cellulose acetate membrane.

3. The novel separation membrane column based on the synergistic decontamination of multiple green adsorbents according to claim 1, characterized in that... The cellulose acetate / chitosan composite fiber membrane is based on a 5wt% cellulose acetate solution and a 5wt% chitosan solution, and the mass ratio of the two solutions is 1:

1.

4. A novel separation membrane column based on the synergistic decontamination of multiple green adsorbents according to claim 4, characterized in that... The cellulose acetate / chitosan composite fiber membrane is prepared by dissolving cellulose acetate solution in acetic acid / dichloromethane; and by dissolving chitosan in a high-concentration acetic acid solution. The ratio of acetic acid to dichloromethane is 1:2, and the ratio of acetic acid to deionized water is 9:

1.

5. A novel separation membrane column based on the synergistic decontamination of multiple green adsorbents according to claim 4, characterized in that... The specific parameters for electrospinning the cellulose acetate / chitosan composite fiber membrane are as follows: temperature 15-25℃, humidity 50%, positive spinning voltage 18kV, negative spinning voltage -2.5kV, spinning rate 0.15-0.25mm / min, distance between spinneret and receiver 18cm, and spinning time 1-3h.

6. A novel separation membrane column based on the synergistic decontamination of multiple green adsorbents according to claim 1, characterized in that, The mixed zeolite has a mass ratio of natural zeolite to Fe-doped zeolite of 2:

1.

7. A novel separation membrane column based on the synergistic decontamination of multiple green adsorbents according to claim 1, characterized in that, The Fe-doped zeolite was added to a mixed solution of NaCl and FeCl3 at a ratio of 10g / 100mL and reacted for 1h in a water bath at 80℃ and 200-300r / min. The mixed solution of NaCl and FeCl3 was prepared by mixing 10% FeCl3 solution and 10% NaCl solution in a volume ratio of 1:

1.

8. A novel separation membrane column based on the synergistic decontamination of multiple green adsorbents according to claim 1, characterized in that, The Fe-doped zeolite is calcined in a muffle furnace at a heating rate of 3-5℃ / min, a holding temperature of 400-500℃, and a holding time of 1.5-2.5h, followed by natural cooling.

9. A novel separation membrane column based on the synergistic decontamination of multiple green adsorbents according to claim 1, characterized in that... A novel separation membrane column based on the synergistic decontamination of multiple green adsorbents is proposed. The column is loaded with N-doped biochar, a composite fiber membrane of cellulose acetate / chitosan, and a mixed zeolite composed of Fe-doped zeolite and natural zeolite. The components are filled in according to a certain mass-volume ratio with the wastewater, wherein the N-doped biochar is 15-25 g / L, the composite fiber membrane is 1-2 g / L, and the mixed zeolite is 7-15 g / L.

10. A novel separation membrane column based on the synergistic decontamination of multiple green adsorbents according to claim 1, characterized in that... A novel separation membrane column based on the synergistic decontamination of multiple green adsorbents is disclosed. The hollow column loaded with activated adsorbent has the same height and inner diameter, and the upper and lower ends of the middle section are both porous filter plates, which can be clamped to fix the membrane on both sides. Among them, the N-doped biochar corresponds to the hollow column at the top, with an inlet and a removable cover. The bottom end is connected to the middle and upper sections of the microfiltration stage porous filter plate and the joint between the middle and lower sections of the cylinder. The upper part is the microfiltration stage porous filter plate, and the lower cylinder is the coarse filtration stage porous filter plate. The mixed zeolite is located in the semi-enclosed hollow cylinder at the bottom, with the coarse filtration stage porous filter plate at the top. The filter plates and the cylinder are integrated, and the filter plates are fixed to the outer edge of the filter plates with screws.